(untitled) (Research, Society and Development, 2021)
Introduction - The present study investigated and presents the Coping Strategies most used by health professionals of a hospital located in the interior of the Legal Amazon, which was adapted to be a reference against the pandemic caused by the new Coronavirus. Objectives - We sought to identify and describe the coping strategies related to the performance of health professionals in fighting the Covid-19 pandemic. Methods - This is a qualitative, descriptive and exploratory study, developed with 100 health professionals working in a reference hospital for critically ill patients during the pandemic. Methods. The data were collected from March to April 2021, through a structured interview and application of the Toulousian coping scale. Results - We noticed a prevalence in relation to the coping strategy of control among the professionals interviewed. It is believed that control is linked to professional practice and immediate decision making, which is constantly present among health professionals. These coping strategies are used as a resource to minimize the suffering inherent to daily changes and adaptations. Conclusion - it is necessary to conduct further studies regarding the emotional and behavioral aspects experienced by health professionals, despite the increase in the production of data that show regional characteristics, they are still incipient to portray the reality.